6x-1-(3x-3)=3

Simple and best practice solution for 6x-1-(3x-3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-1-(3x-3)=3 equation:



6x-1-(3x-3)=3
We move all terms to the left:
6x-1-(3x-3)-(3)=0
We add all the numbers together, and all the variables
6x-(3x-3)-4=0
We get rid of parentheses
6x-3x+3-4=0
We add all the numbers together, and all the variables
3x-1=0
We move all terms containing x to the left, all other terms to the right
3x=1
x=1/3
x=1/3

See similar equations:

| 2700=6800x | | 8x^2=500 | | 7x+31=10 | | 40÷3q=15 | | 3(x+5)/4+-7(x+3)/10=4 | | 3x/8-3=-5 | | 3*x+x/5-5=1/5+5*x | | 5/8t+14=-1 | | 4q+20=16 | | 12(t+4)-8=88 | | 1/5x+1/3=-1 | | 8c-6=15 | | 2x-8=130 | | x-5/3+4x-9/12=5x-32/9-x+9/21 | | 2(3x+5)=x^2 | | 5t-3=2t+4 | | 186=x-x(.07) | | 2x2-6=3x | | 7x-35=70 | | -6(1-7n=36 | | 10x+7=-14+x | | -6(7x+8)=36 | | -6(-7n-8=-8 | | (x+5)^2+9(x+5)+14=0 | | 80+5x=90 | | P=300+2x | | 6=3-n | | -2(4k+6=-60 | | 3x2+1-3x2-1=216 | | 8(-7x-8)=-8 | | 5=9w-8 | | 6z/5=6 |

Equations solver categories